PENDIDIKAN KARAKTER DALAM PERSPEKTIF AGAMA BUDDHA - Rendy Arifin (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
Character education in Indonesia is continuously echoed especially in the midst of the current digital era. Every religion will certainly form a good and moral character for its people, and Buddhism is no exception. This research tries to review this. Character education in Buddhism is closely related to the Ariya Aṭṭhaṅgika Magga/Noble Eightfold Path, where there is a core character that is intended as a Buddhist. Character education in Buddhism is emphasized on the mind. First it starts with controlling the mind, then proceeds with the speech and actions of the body. Mind control is done the first time not without reason. This is inseparable because the mind is the forerunner of all actions. So the good or bad character that appears in a person, must start from his mind. In Buddhism there are three roots of evil, namely hatred (dosa), greed (lobha), and delusion (moha), which have the potential to give rise to bad characters. Therefore, the development of giving (dana), maintaining morality (sila), and developing the mind (bhavana) needs to be increased to eradicate the three roots of evil. Character education in Buddhism should be taught repeatedly so that it becomes a good habit and can be passed on to the next generation. Not killing, not stealing, not committing immorality, not lying, not getting drunk or taking drugs, spreading love, and sympathy are some of the behaviors that emerge from Buddhist character education.